Alcohol and the nervous system - Sullivan, Edith V.; Pfefferbaum, Adolf (Handbook of clinical neurology, 2014)
Alcohol is the most widely used drug in the world, yet alcoholism remains a serious addiction affecting nearly 20 million Americans. Our current understanding of alcohol''s effect on brain structure and related functional damage is being revolutionized by genetic research, basic neuroscience, brain imaging science, and systematic study of cognitive, sensory, and motor abilities. Volume 125 of the Handbook of Clinical Neurology is a comprehensive, in-depth treatise of studies on alcohol and the brain covering the basic understanding of alcohol''s effect on the central nervous system, the diagn.